Bank management & financial services - Rose, Peter S. (McGraw-Hill/Irwin, 2008)
Bank Management and Financial Services is designed to help students master established management principles and to confront the perplexing issues of risk, regulation, technology, and competition that bankers and other financial-service managers see as their greatest challenges for the future. The seventh edition is the most up-to-date discussion of the newest banking and financial-services laws and regulations currently available, encompassing provisions of the new federal consumer bankruptcy rules (the first major changes in the U.S. bankruptcy code in nearly 30 years) as well as the newest rules concerning electronic banking, customer privacy, and the first major reforms in the FDIC insurance system in more than a quarter of a century. Bank Management and Financial Services also remains the most readable and engaging text on the market, with a plethora of real-world examples and information